ISSUES OF FEMINISME IN THE PATRIARCHAL SOCIETY AS PORTRAYED IN ANANTA TOERâ€™S â€œTHE GIRL FROM THE COASTâ€ - Zumam, Wildona (Jurnal Pendidikan Bahasa dan Sastra, 2014)
This article revolves around the issues of feminism in a novel. Issues of feminism are interesting to analyze because they have been leading issues in many societies. There are two problems addressed, namely what issues of feminism are and how the main character reacts to her condition in the novel. Marxist and feminism theories are used to analyze the position of the main character. Results indicate the girlâ€™s tiresome yet fruitless struggle against the patriarchal oppressions in her unequal marriage and there is no victory for a woman except she is willing to leave her life behind. The novel is suitable for use in literature and also good for reading activities in an intermediate to advanced English class